Low sEng Level in Preeclampsia with MFTHFR Gene Polymorphism Suggesting a Protective Factor - Pramono, M. Besari Adi; Faradz, Sultana MH; Suhartono, Suhartono; Susanto, Hardhono; Rachmawati, Banundari; Pramono, Noor (Journal of Biomedicine and Translational Research, 2025)
Background: Preeclampsia is one of the most serious complications of pregnancy and the leading cause of maternal and fetal mortality. Various studies have shown that Glutathione Peroxidase (GPx) deficiency and increased Soluble endoglin (sEng) level are consistently associated with the incidence of preeclampsia. Several studies also show the role of MTHFR A1298C and C677T gene polymorphisms in preeclampsia.Objective: This study investigated association between blood GPx, sEng levels, MTHFR A1298C and C677T gene polymorphisms in Preeclampsia.Methods: This analytic observational case-control study was conducted on 70 cases of preeclampsia and 70 controls. Blood GPx and sEng levels were measured using Enzyme Linked Immunosorbent Assay (ELISA). MTHFR A1298C and C677T gene polymorphism was genotyped using Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP). The data obtained were analyzed using the Mann-Whitney U test, chi-square test, and independent T-test.Results: There were no significant differences in GPx levels or MTHFR A1298C/C677T genotype distribution between groups. sEng levels were significantly higher in the preeclampsia group than controls (p=0.001). ROC analysis identified a cut-off of 7.75 ng/mL. Among preeclampsia patients, those with the MTHFR 1298AC/CC genotypes had lower sEng levels than wildtype (p=0.027), suggesting a potential protective effect. No association was found for C677T.Conclusion: We found no significant difference in GPx level, MTHFR A1298C and C677T gene polymorphism between preeclampsia and control group. Soluble endoglin (sEng) level in the preeclampsia group (mean: 11.0±5.22) were significantly different (p=0.001) compared to the control group (mean: 8.1±5.31). Increased level of sEng is associated with incidence of preeclampsia. A key finding in this study is the significantly lower sEng levels observed in preeclampsia patients carrying the MTHFR 1298AC and 1298CC alleles compared to the control group (p=0.027). This indicates a protective factor where in preeclampsia with MTHFR gene alleles 1298AC and 1298CC sEng levels are lower compared to wildtype.